2015
DOI: 10.1186/s13018-015-0290-9
|View full text |Cite
|
Sign up to set email alerts
|

Zero-profile implant versus conventional cage-plate implant in anterior cervical discectomy and fusion for the treatment of degenerative cervical spondylosis: a meta-analysis

Abstract: BackgroundZero-profile implant has become more and more popular in anterior cervical discectomy and fusion (ACDF) for the treatment of degenerative cervical spondylosis. However, there was no enough evidence judging its efficiency and safety. The aim of this analysis was to evaluate the efficacy and safety of Zero-profile implant compared with conventional cage-plate (CCP) in ACDF.MethodsAll studies directly comparing the outcomes between the Zero-profile implant and CCP implant in ACDF were included, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…Evidence supports utilization of cervical standalone implants, either along the whole construct or above C4, to decrease the chances of dysphagia. 3,17 Further, a prolonged anterior approach lasting more than 3 hours, particularly with longus coli muscle retraction, is likely responsible for higher prevertebral soft-tissue swelling and resultant higher rates of dysphagia and prolonged intubation. Use of narrow blades and intermittent longus retraction may help obviate some of the complications.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports utilization of cervical standalone implants, either along the whole construct or above C4, to decrease the chances of dysphagia. 3,17 Further, a prolonged anterior approach lasting more than 3 hours, particularly with longus coli muscle retraction, is likely responsible for higher prevertebral soft-tissue swelling and resultant higher rates of dysphagia and prolonged intubation. Use of narrow blades and intermittent longus retraction may help obviate some of the complications.…”
Section: Discussionmentioning
confidence: 99%
“…Stand-alone cages afford comparable mechanical stability and efficacy compared to anterior plating, but current literature is polarizing with regard to their complication incidence. 14 - 17 Additionally, no studies have directly compared cases performed utilizing a plate or stand-alone cage with respect to length of hospital stay or ability to send patients home the same day of surgery. 18 …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to provide similar biomechanical stability to the use of a cage and anterior plating system [ 13 ]. The same conclusion was drawn from a study involving patients with degenerative pathology, and the Zero-P has been used in ACDF for the treatment of degenerative cervical disease [ 14 ]. However, these previous studies did not provide sufficient evidence on the efficiency or safety of Zero-P in traumatic cervical disc injury.…”
Section: Introductionmentioning
confidence: 59%
“…Additionally, Njoku et al [ 11 ] reported that the Zero-P had clinical outcomes and radiologic fusion rates comparable with the cage-plate system. Most studies have assessed the postoperative outcomes of ACDF using Zero-P in cases of degenerative cervical spondylosis, Zero-P has been accepted as a useful graft for ACDF in degenerative cervical disc disease [ 2 , 4 , 11 , 14 , 16 ]. Based on these previous studies, we used Zero-P as a graft for ACDF in cases of traumatic disc injury.…”
Section: Discussionmentioning
confidence: 99%